2008
DOI: 10.1007/s11340-008-9200-y
|View full text |Cite
|
Sign up to set email alerts
|

The Fracture Process of Tempered Soda-Lime-Silica Glass

Abstract: This work presents experimental observations of the characteristic fracture process of tempered glass. Square specimens with a side length of 300 mm, various thicknesses and a residual stress state characterized by photoelastic measurements were used. Fracture was initiated using a 2.5 mm diamond drill and the fragmentation process was captured using High-Speed digital cameras. From the images, the average speed of the fracture front propagation was determined within an accuracy of 1.0%. Two characteristic fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 20 publications
5
39
0
6
Order By: Relevance
“…This is verified by the fact that the fracture propagated in the tensile region first and then in the compressive layer over a period of time". However, in more recent work, (Nielsen et al 2009;Dugnani et al 2014) it is shown experimentally and analytically that the surface regions are cracking (almost) simultaneously with the center part. It is therefore decided, in the present work, to investigate the total strain energy in a fragment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is verified by the fact that the fracture propagated in the tensile region first and then in the compressive layer over a period of time". However, in more recent work, (Nielsen et al 2009;Dugnani et al 2014) it is shown experimentally and analytically that the surface regions are cracking (almost) simultaneously with the center part. It is therefore decided, in the present work, to investigate the total strain energy in a fragment.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors, (Barsom 1968;Nielsen et al 2009), have drilled with diamond tipped drills into the tensile zone, in order to minimize the energy added to the system. In these cases, it is reasonable to assume, that only the stored strain energy, from the residual stresses, are driving the fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…1 The sudden release of strain energy will cause the glass to fragmenting at such high speed, that the fragments are accelerated and, if not hindered, they will move in an explosive manner, see e.g. Nielsen et al (2009). There are primarily in-plane residual stresses in the tempered glass, the displacement of the glass fragments will therefore only be in the plane of the glass plate, Fig.…”
Section: The Tempering Processmentioning
confidence: 99%
“…Gulati applies the analytical model developed by Barsom (1968) to estimate the same frac-tion and finds that 35% of the initial strain energy is used. Nielsen et al (2009) presents a study of the fracture process of tempered glass. The fracture process is initiated with a diamond drill to transfer a minimum of energy to the test specimens.…”
Section: The Tempering Processmentioning
confidence: 99%
See 1 more Smart Citation